1993
DOI: 10.1021/bi00063a012
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a yeast DNA polymerase .alpha. complex with associated primase, 5'.fwdarw.3' exonuclease, and DNA-dependent ATPase activities

Abstract: We have purified a multimeric form of yeast DNA polymerase alpha with DNA polymerase, primase, 5'-->3' exonuclease, and single-stranded (ss) DNA-dependent ATPase activities to near-homogeneity. The molecular mass of complex was 650 kDa with subunits ranging in sizes from 30 to 180 kDa. The alpha-subunit of the complex could be detected by DNA polymerase alpha antibody. No cross-reactivity of polypeptides within the complex was observed with antibodies directed against polymerase delta or epsilon. The multimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Characterization of the 5′ f 3′ Exonuclease Associated with the DNA Polymerase R Complex. Previously we have purified a complex of DNA polymerase R with an associated 5′ f 3′ exonuclease activity (Biswas et al, 1993a). In order to characterize this nuclease activity, we have purified the protein to homogeneity using a multistep purification procedure, as described above.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Characterization of the 5′ f 3′ Exonuclease Associated with the DNA Polymerase R Complex. Previously we have purified a complex of DNA polymerase R with an associated 5′ f 3′ exonuclease activity (Biswas et al, 1993a). In order to characterize this nuclease activity, we have purified the protein to homogeneity using a multistep purification procedure, as described above.…”
Section: Resultsmentioning
confidence: 99%
“…We reported earlier the presence of a 5′ f 3′ exonuclease activity that copurified with DNA polymerase R-primase complex from the yeast S. cereVisiae (Biswas et al, 1993a). In order to decipher the role(s) of the exonuclease in the chromosomal DNA replication, it was essential to develop a method of purification of this exonuclease activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier we have shown that a 5′ f 3′ exonuclease copurifies with DNA polymerase R-primase (pol R) complex (Biswas et al, 1993a). Purification of this nuclease from S. cereVisiae and determination of its identity as the RTH1 5′ f 3′ exonuclease have been described earlier (Zhu et al, 1997).…”
mentioning
confidence: 94%